Computer-assisted creativity: Emulation of cognitive processes on a multi-agent system - López-Ortega, Omar (Expert systems with applications, 2013)
► Synthesis of cognitive processes associated to creative thinking. ► Emulation of cognitive processes via software agents. ► AUML modelling and implementation of a multi-agent system aimed at assisting in creative tasks. ► Planning and divergent exploration exemplified. For creativity to be computed, it is paramount to understand the cognitive processes involved, which have been elucidated by either surveying creative people or discovering regions of the human brain that activate during creative endeavors. From this scattering, the author proposes a holistic framework to describe them and their interaction. Hence, creativity can be regarded as a meta process which coordinates autonomous cognitive processes such as planning or divergent thinking. To represent the interplay of cognitive processes around creativity, models are developed in the Agent Unified Modeling Language (AUML). Then, the execution of each process is delegated to autonomous agents and a global coordination protocol is devised. The implementation of the MAS is done on the JADE platform. Two modules of the resultant system are exemplified: opus planning and divergent exploration. The coordination protocol is also presented. The domain in which the software system is tested is the creation of musical pieces.